Non-conceptual normative pluralism and the dualism of practical reason - Hambly, Jesse (Utilitas, 2024)
According to normative pluralists there are no truths about what one ought simpliciter to do, only truths about what one ought to do according to some normative system or standpoint. In contrast with conceptual normative pluralists who argue for this conclusion on the basis that the concept of an ought simpliciter is somehow defective, non-conceptual normative pluralists defend this conclusion on first-order grounds. Non-conceptual normative pluralism has recently received a book-length defence by Mathea Slåttholm Sagdahl. In this article I critique Sagdahl's defence of non-conceptual normative pluralism. Firstly, I challenge Sagdahl's attempt to motivate non-conceptual normative pluralism by appealing to Henry Sidgwick's work on the dualism of practical reason. Secondly, I criticise her response to the most prominent argument against non-conceptual normative pluralism in the philosophical literature, the argument from nominal-notable comparisons. Thirdly, I explore the possibility of a view similar to Sagdahl's position but which accepts the ought simpliciter.